Environmental protection and economic offenses: Advantages and disadvantages - Lukić Natalija (Glasnik Advokatske komore Vojvodine)
The forms of criminal activity harming the environment are diverse. Due to the drastic consequences affecting both the environment and human health and life, various international organizations list these activities at the very top of dangerous and growing criminal phenomena. This can be attributed to the inadequate application of criminal law in combating environmental crime and the replacement of this branch of law in practice by other legal mechanisms. The subject of this paper is an analysis of economic offenses as specific offenses within the domestic legal system, as well as their advantages and disadvantages in protecting the environment. The paper first points to the basic characteristics of economic offenses. The author analyzes the concept of economic offenses and the conditions for liability. The second part compares the similarities and differences with the criminal liability of legal persons. Finally, the paper highlights the advantages and disadvantages of the system of economic offenses.